(البيئة العربية ودورها في تنمية مهارة الكلام (دراسة متعددة في معهد الأمانة الحديث كريان سيدووارجو و معهد دار الحكمة الحديث تاوانج ساري تولونج أجونج - Faiqoh, Putri Kholida (Institut Agama Islam Negeri (IAIN) Kediri, 2018)
Language Environment Approach (Bi’ah Lughowiyah) is a language learning approach that aims to enhance the ability of learners in a foreign language through the utilization of the environment as a learning resource. Speaking skills (Maharah Kalam) are one type of productive skills of learners who require the ability to pronounce sounds correctly, it is a major part of the curriculum of foreign language learning. The Al-Amanah Islamic Boarding School and Darul Hikmah Islamic Boarding School is two of the cottages that there are several activities that aim to develop the ability to speak with students in Arabic, such as Mufrodat Kulla Yaum, Usbu' al-'Araby, Muhadharah, and all of activities about daily speaking skills until monthly. But unfortunately, most students of this cottage did not speak Arabic correctly because mixed by language of their region (Jawa). This research uses a qualitative approach, as well as the type of Multisite research. The results of this study are: 1) The role of Bi'ah Arobiyah in developing Maharah Kalam at the cottage, in terms of the psychological, the role is very helpful, but less. In terms of pedagogic, the role is ineffective. In terms of instructional, there is major role. 2) Supporting factors of Bi'ah Arobiyah that affect the ability of students to speaking Arabic, the position and the positive appreciation of all the inhabitants of the cottage to the Arabic language, Arabic learning materials, Language Activator Division of cottage, rules and punishment, the implementation of the teaching-learning processing a fun atmosphere, and strong motivation of most students. And the inhibiting factors are: the lack of a good education funding for the implementation of Bi'ah Arobiyah, at least media language learning, and most students of this cottage did not speak Arabic correctly because mixed by language of their region. And to solve the problems, intensive evaluation followed by corrections in learning is needed.